Socialization of Limestone Utilization to Reduce Iron Levels in Clean Water - Irvan, Ulva Ria; Farida, Meutia; Thamrin, Meinarni; Maulana, Adi; Alimuddin, Ilham; Umar, Hamid; Maulana, Baso Rezki; Sahabuddin, Sahabuddin; Tonggiroh, Adi; Ma'waleda, Musri; Yanny, Yanny; A. Mallarangeng, Nurjinaan Fakri (Faculty of Engineering UNHAS, 2024)
The problem of clean water with high iron content significantly impacts the quality of life of people in Indonesia, including in Mangasa Village, Tamalate District, Makassar. Residents face reddish wells, tap water, and a metallic odor caused by geological factors or old and rusty pipes, which pollute water sources and endanger health. As a solution, Community Service activities by the Geological Engineering Department of Hasanuddin University socialize the use of limestone to reduce iron levels in water. This socialization results from a collaboration between the Community Service team and the capstone design team of geological engineering students at Hasanuddin University in designing clean water filters. The activity began with delivering educational materials regarding water quality problems and the benefits of limestone, accompanied by easy-to-understand visualizations. After a pre-test was conducted to measure initial understanding, the community service team presented and simulated limestone utilization, followed by an interactive question and answer session. Then, a post-test was conducted to evaluate the increase in participants' understanding, which was analyzed to measure the effectiveness of the socialization. The evaluation results showed a significant increase in participants' knowledge of clean water quality, the impact of iron content, and the use of limestone as a filter, which was 72%. This increase reflects the high enthusiasm and motivation of the community in adopting clean water treatment methods.